A Study on the Impact of Digital Marketing on the Business Growth of SMEs Warkop Sidjie - Rismawati; Siti Nuraini; Adelia Dwi Sagita; Shavira Nafa Dilla; Muhammad Yusuf (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the impact of digital marketing on the business growth of Micro, Small, and Medium Enterprises (MSMEs) Warkop Sidjie. In the current digital era, implementing digital marketing strategies has become crucial for MSMEs to enhance their visibility and competitiveness. This research employs a quantitative approach by collecting data through surveys involving the owners and visitors of Warkop Sidjie. The collected data is analyzed using linear regression to measure the relationship between digital marketing variables and business growth. The results of the study indicate a significant positive impact of digital marketing on the business growth of Warkop Sidjie. The use of social media as a promotional tool, websites, and other digital marketing strategies has proven effective in increasing the number of customers and sales. Moreover, survey results reveal that customers who discover Warkop Sidjie through digital platforms tend to visit more frequently. This study provides practical implications for other MSMEs to utilize digital marketing as a strategic tool to expand their market share and boost business growth.